Regional disparities in India - Nair,K.R.G.(Editor) (Akansha Pub. House, 2001)
Contributed articles presented in a National Workshop on Regional Disparities organised by the Omeo Kumar Das Institute of Social Change and Development, Guwahati, during 1996.